Influence of monaural auditory stimulation combined with music on brain activity - Chang, Ming; Tanaka, Kenta; Naruse, Yasushi; Imamura, Yasuhiko; Fujii, Shinya (Frontiers in Human Neuroscience, 2024)
Introduction Recently, the increasing attention to mental states and psychophysical health has fueled the research into methods that can aid in relaxation and recovery. Traditional methods like meditation and sauna, while effective, have their limitations; thus, the need for more accessible and convenient alternatives. Methods Our innovative approach combines monaural beats with music, attempting to replicate the relaxing effects of a sauna in the auditory domain. Results In comparison to normal music and silent condition, the power of the theta active band significantly increased when listening to our modified music. Furthermore, after listening to modified music, there was a significant increase in mismatch negativity (MMN) amplitude in the oddball task. Additionally, participants’ subjective responses to a questionnaire indicated significant changes in body relaxation and other metrics after listening to the processed music. Discussion This state is considered similar to the “totonou” state, which manifests in physical and mental feelings of relaxation, pleasure, and mental clarity in the sauna. Thus, the present research proposes a convenient method for achieving relaxation, opening an avenue for individuals to customize their “totonou” music based on personal preferences.